O pensamento socrático: a busca da verdade e sua influência na investigação policial - Carrasco, Carlos José Fávaro (2013)
This essay explains, in short, the Socratic thought left as a legacy to the world by the great philosopher Socrates (Athens, 470 or 469 BC - 399 BC), who, throughout his life, sacrificed his personal ambitions for the sake of their fellow citizens. Know thyself and I just know that I know nothing demonstrate his relentless yearning for wisdom, the greatest virtue, and being fair, the greatest happiness. This work makes us reflect about his own method in the search for truth/knowledge. We will see his influence in current police investigation methodologies, regarding the peculiarities applicable to each case and the terms of a criminal offense, in relation to the relevance of the work of the Judicial Police to identify authorship, circumstances of the crime, as well as its motivation, in order to enable the prosecution of the offenders